Webcam Preschool Stuttering Treatment: Outcomes and Experiences from a Clinical Trial. (30th June 2015) - Bridgman, K.; Block, S.; Onslow, M.; O'Brian, S.; Jones, M.
Abstract: Early treatment provides children who stutter with the best opportunity to avoid the lifelong complications associated with stuttering. Currently many children are unable to access treatment due to distance and lifestyle factors. One solution to this problem is to deliver the treatment using webcam. This service delivery model can: (1) improve access to evidence based best practice stuttering treatment for children, (2) improve access to specialist clinicians and quality services, (3) reduce costs and resources involved with outreach service provision and (4) provide more convenient home-based treatment for young children. The aim of this clinical trial was to show non-inferiority of early stuttering treatment by webcam compared to standard in-clinic methods. The design was a parallel, open plan, Phase III non-inferiority randomised controlled trial with 49 children randomised. The control group received standard delivery of treatment in a traditional clinic setting. The experimental group received the same treatment within their homes, using a computer and webcam. Primary outcomes were numbers of consultations and clinician hours to attain levels of no stuttering or nearly no stuttering. Secondary measures were stuttering severity ratings. Additional information was obtained from parent questionnaires and the experience of the treating clinician. Results are reported for primary and secondary outcomes, with particular attention to parent reports about webcam rapport with the clinician, webcam rapport between child and clinician, webcam ease of parent treatment and learning and logistics of webcam early intervention. Unexpected clinician observations are also reported for webcam treatment. These include convenience, treatment readiness, defining the clinical space and trends in clinical transfer. In qualitative and quantitative terms, webcam early intervention is feasible and successful. This presentation concludes with a discussion of the clinician's role, consultation logistics, future directions and community translation.